Quality Assessment of YouTube Videos as an Information Source for Testicular Torsion - Bai, Gaochen; Pan, Xi; Zhao, Tianxin; Chen, Xiong; Liu, Guochang; Fu, Wen (Frontiers in Public Health, 2022)
Background: Testicular torsion is an acute scrotal disease requiring urgent management, and the COVID-19 pandemic has been demonstrated to lead to poor outcomes for this disease. Presently, many people tend to seek health information via YouTube. This study aims to quantitatively assess the quality of English YouTube video content as an information source of testicular torsion. Methods In this cross-sectional study, a search was performed with the search term “testicular torsion” on YouTube, and the first 100 videos listed by relevance were selected for our analysis. Duplicate, non-English, videos without audio and surgical videos were excluded. Video features (duration, number of days online, views, likes, comments), source of the video, and author's country were collected. Each video included in the study was assessed using DISCERN and Journal of the American Medical Association (JAMA) Benchmark Criteria. A correlation analysis was performed considering video features, video source, DISCERN scores and JAMA scores. Results A total of 66 videos were included and analyzed. The most common video content was general information, including etiology, symptoms, and treatment. The majority of videos were from education and training websites (30%), physicians (23%), and independent users (21%). The mean DISCERN and JAMA scores were 36.56 and 2.68, respectively. According to DISCERN, the quality of video uploaded by physicians was relatively high (P < 0.001), and the quality of video uploaded by independent users was relatively low (P < 0.001). The JAMA score had no relevance to the video source (P = 0.813). The correlation between the video features, DISCERN and JAMA scores was controversial by different assessment methods. Conclusions Despite most of the videos on YouTube being uploaded by medical or education-related authors, the overall quality was poor. The misleading, inaccurate and incomplete information may pose a health risk to the viewers, especially during the COVID-19 pandemic. Much effort needs to be undertaken to improve the quality of health-related videos regarding testicular torsion.